2014
DOI: 10.1097/bsd.0b013e318272faaf
|View full text |Cite
|
Sign up to set email alerts
|

Sagittal Rebalancing of the Pelvis and the Thoracic Spine After Pedicle Subtraction Osteotomy at the Lumbar Level

Abstract: Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…In general, Correlation between spinal parameter and pelvic parameter is important for spinal sagittal balance 11) . The most important correlation is between the PI as anatomical index and the SS as the positional index 7 , 15) .…”
Section: Discussionmentioning
confidence: 99%
“…In general, Correlation between spinal parameter and pelvic parameter is important for spinal sagittal balance 11) . The most important correlation is between the PI as anatomical index and the SS as the positional index 7 , 15) .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated varying proportions of trunk versus pelvic correction based on the spinal pathology and ankylosis. 27,36 While there were correlations between LL correction outside the 3CO and correction of sagittal parameters, this study found no correlation between 3CO and change in radiographic parameters. This could indicate that the 3CO is not the only factor in correction surgery that leads to global realignment.…”
Section: Figmentioning
confidence: 52%
“…This result echoes the findings of Rousseau et al, who studied 356 patients undergoing 3CO for the treatment of ASD. 35,36 Their results demonstrated no significant impact of pedicle subtraction osteotomy level on postoperative PT or T1SPi. One specific finding of the current study relates to the correlation between change in PT and location of the postoperative apex of the lumbar curve (R = -0.175, p < 0.05).…”
Section: Figmentioning
confidence: 91%
See 1 more Smart Citation
“…Chen et al [22] asserted that structural damage to the hips can contribute to mobility limitation, functional impairment, and the inability to exercise. Rousseau et al [23] studied the spinal balance of 356 patients and determined that spondylarthritis cases showed less pelvic reorientation after lumbar PSO, probably due to limitations in hip mobility.…”
Section: Discussionmentioning
confidence: 99%